Digital Literacy and Privacy Resilience: Navigating Data Vulnerability among University Students - Nazhifah; Adriansyah Muftitama; Nurdhini Tsabitulchusna (Profetik: Jurnal Komunikasi, 2026)
The rapid growth of social media among university students has led to an escalation of data exploitation and privacy breaches. This study aims to investigate how digital literacy functions as a proactive resilience strategy among students of Universitas Muhammadiyah Riau, focusing on how the four pillars of digital skills, ethics, safety, and culture contribute to safeguarding personal information. Using a descriptive qualitative approach with purposive sampling, data were collected through documentation, observations, and in-depth interviews with four active Instagram users, including campus influencers. The findings reveal that students demonstrate strategic resilience by actively applying digital literacy as a defense mechanism. They utilize advanced security settings, such as two-factor authentication, perform critical source verification to mitigate misinformation, and maintain boundaries between personal and professional digital identities to manage their online reputation. Furthermore, students display ethical responsibility and data security practices, enhancing their adaptive capacity against systemic privacy threats. This study concludes that digital literacy serves as a crucial strategic instrument to maximize internet benefits while mitigating unanticipated privacy risks. The novelty lies in redefining digital literacy as a performative resilience strategy rather than a passive skill set for navigating modern data vulnerabilities